Peranan teknologi terhadap perubahan sosial - mardani, muhamad (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the impact of technological development on the lives and social interactions of Indonesian people. Advances in information and communication technology (ICT) have changed the way people communicate, interact, and live their daily lives. In this ever-evolving digital era, it is important to understand how these changes affect social dynamics in Indonesia. This research is based on a literature analysis from various sources, such as websites, articles, and academic publications discussing the impact of technology in Indonesia, as well as examining related case studies and surveys.The research findings indicate that the use of technology, especially social media, instant messaging applications, and other online platforms, has connected people from various social, cultural, and geographical backgrounds. This facilitates communication across regions and social groups and expands opportunities for cultural exchange. However, challenges also arise, such as the potential for social isolation due to excessive technology use, which reduces face-to-face interaction. Furthermore, personal data privacy issues are also a major concern, considering the potential for violations by large technology companies. Unequal access to technology in some regions of Indonesia also remains an issue that needs to be addressed.The use of social media, instant messaging applications, and other online platforms has connected people from diverse social, cultural, and geographical backgrounds. This has facilitated cross-regional and cross-social group communication, as well as opened up opportunities for broader cultural exchange. However, besides the positive impacts.